2009
DOI: 10.1177/0040517508097520
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Behavior of Microencapsulated Fragrances on Cotton Fabrics

Abstract: Abstract.Microencapsulated products are very common in some fields such as pharmacy and the textile industry has recently incorporated them into their products. Firstly, this research assessed the presence of flavour microcapsules on cotton fabric using different padding applications and evaluated them using Scanning Electronic Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). When the OH stretching region between 3700-3000 cm -1 from spectra are examined, we propose some area ratios to quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Nowadays, textile industry shows a growing interest into the functionalization of textiles for innovative commercial applications. The emerging technologies based on microencapsulation are able to confer new properties and add value to the textiles that are not possible or cost‐effective using other technologies 1–3…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, textile industry shows a growing interest into the functionalization of textiles for innovative commercial applications. The emerging technologies based on microencapsulation are able to confer new properties and add value to the textiles that are not possible or cost‐effective using other technologies 1–3…”
Section: Introductionmentioning
confidence: 99%
“…Several methods of incorporating PCM microcapsules into a fibrous structure have been developed. The microcapsules can be applied by stamping works, exhaustion dyeing, impregnation, spraying and coating or by direct incorporation in the fiber without highly modifying its touch and color 3, 11, 12. In previous applications of PCM technology in the textile industry, for garments and home furnishing products, microencapsulated PCM were incorporated into acrylic fibers6 or polyurethane foams13 or were embedded into a coating compound and topically applied to a fabric 14.…”
Section: Introductionmentioning
confidence: 99%
“…As is evident from Figures 1.a -5.a, the microcapsules are of very regular spherical shape, without any deformations or changes in their shell. The authors in [20] also confirmed the fact that there were no transformations in peppermint microcapsules applied on cotton fabric heated by air at 120 °C. Additionally SEM analysis showed that with an increase in the temperature of up to 160 °C, the swelling was reduced considerably.…”
Section: Resultsmentioning
confidence: 56%
“…The yarn samples grafted with Eucalyptus microcapsules were analysed by SEM, which was a good technique for other qualitative research [3,20,29]. Researches in [3] confirmed that the effect of changing the concentration of micro-spheres in dispersion can be easily observed from SEM micrographs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation